Mauvaises réputations ? - Fatia Terfous; Géraldine Rix-Lièvre (Communication)
Many observers (managers, researchers, athletes) have criticized the way referees are treated in the media in France and elsewhere. Until now, no study has examined media representations of referees and/or rule enforcement in sports. The authors set out to describe how the press treats referees and examine how they are perceived and judged during World Cup events. More broadly, they aim to uncover the underlying arguments and discursive strategies adopted by the press in framing these events, as well as the links between the sports trade press and public authority figures of law and order.